Empowering Single Mothers Group of Jasmine Strand Entrepreneurs Through Marketing and Financial Reporting Training - Nurrahmawati, An; Sangka, Khresna Bayu; Perwitasari, Dian; Juwita, Aulia Hapsari; Bintariningtyas, Selfia; Maarif, Miftachul (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to increase the knowledge and skills of the single mothers in entrepreneurial activity on the Jasmine strand regarding marketing, financial, and administration reporting knowledge. The method stages carried out in this activity were the combination method of interviewing, socializing, discussing, mentoring, and evaluating. The evaluation used a questionnaire, and the results were analyzed using descriptive techniques. The results of this activity showed that the members of this entrepreneurial group understood how to market their product better, conventionally and digitally. These SMEs also now better understand and apply the financial and administration recording matter. The evaluation result shows that most of the audience feels the training is valuable and easy to understand.